Shifting Prevalence Patterns for Special Educational Needs in the Era of Response-to-Intervention Policy - Hall-Mills, Shannon (Frontiers in Education, 2021)
The Response to Intervention framework provides tiered levels of support in general education (K-12) to improve student outcomes and may relate to special education determinations. While broadly applied to eligibility determinations for children with specific learning disability, the Response to Intervention model also presents an interesting consideration for children with language impairment. The requirement of the Response to Intervention framework in education policy may have a significant impact on the identification and eligibility processes for children with special educational needs. The purpose of the present study was to explore whether this policy implementation altered the prevalence of students with disabilities ages 3 to 21 years who were determined to be eligible for special education under the categories of specific learning disability and language impairment. Longitudinal data was examined to determine whether significant changes occurred in the prevalence rates in a state that mandated implementation of Response to Intervention policy. The results revealed that significant changes occurred in the prevalence rates from pre- to post implementation of Response to Intervention policy; language impairment prevalence increased and specific learning disability prevalence decreased. Prevalence changes have maintained over multiple subsequent school years. The findings have important implications for policy and practices focused on the identification of these common disabilities throughout the school years.